Mobilization of Community Groups for Fish Seed Rearing : An Institutional Innovation of Tribal Fisherfolk at Tawa Reservoir, M.P. (Indian Journal of Extension Education, 2009)
The importance of local institutions in natural resource management is widely recognised across the globe. Studies in different countries for different forms of natural resources have empirically shown the success of local groups and institution in management of natural resources. It is believed now that new configuration of social and human relationship are prerequisites for long term improvement in nature. There is growing evidence to show that when people are well connected in groups and networks, and when their knowledge is sought, incorporated and build upon during planning and implementation of conservation and development activities, then they are more likely to sustain stewardship and protection over the long term (Cernea, 1991, Pretty 1995; Singh & Ballabh, 1997; Krishna, 2002; Uphoff, 2002; Mcneely & Scherr, 2003).